Does Digital Transformation Enhance ESG Performance: A Bibliometric Review - Purnomowati, Nasyiah Hasanah; Sutopo, Bambang (LPPM Universitas Terbuka, 2025)
The purpose of this study is to map and analyze the development of the research about the relationship between digital transformation and ESG performance through a bibliometric approach. We use Scopus database in the range of 2020–2025. A total of 169 articles were identified and analyzed using Scopus Analyze menu and the VOSviewer. The bibliometric results show a sharply increasing trend of publications since 2020, and China leads with 95 publications. The analysis of keywords and citations reveals five main clusters that describe the latest research directions. The most frequently cited articles such as the work of Lu (2024) and Wang et al., (2023) are central to the influence in shaping the next direction of research. The implication of this research or academics is that the results of this study open up further research opportunities to deeply explore how digitalization can be useful in an ethical and effective way in improving transparency and accountability of sustainability reporting. For business practitioners, the findings of this research emphasized on the importance of digital transformation development to improve corporate environmental, social, and governance performance.